AI-Enhanced Storytelling: Integrating Visual, Textual, and Auditory Elements Through Multimodality - Pratomo, Evan Raditya (ULTIMART Jurnal Komunikasi Visual, 2024)
This study explores the integration of Artificial Intelligence (AI) in experience design, focusing on its role in creating a multi-sensory experience that bridges visual, textual, and auditory elements. The research centers on the album "Sky of Summer Nights,” where music generated by Suno AI complements illustrations and lyrics created by the author, Evan Raditya Pratomo. The project features three original illustrations, each corresponding to a song: "The Fairy Tale of Pink Summer,” "A Hug for Pink Moon,” and "Freed His Heart.” This research demonstrates how creative expression can be enhanced through multimodal principles, highlighting the challenges of effectively conveying messages through a combination of mediums. The findings affirm that the integration of AI can preserve the integrity of traditional design practices while offering new possibilities for innovation. By applying multimodal design theory, the study illustrates how AI is not only a tool but a catalyst for new emotional and creative experiences across disciplines. This research emphasizes the collaboration between human creativity and Suno AI, driving forward innovation in the fields of visual communication and experience design. Keywords: sky of summer nights; multi-sensory; multimodal; creative expression; suno AI